Arthrocentesis in TMJ Internal Derangement: A Prospective Study - Kuruvilla, V. E. (Springer-Verlag, 2011)
OBJECTIVES OF THE STUDY: To evaluate improvement in symptoms following arthrocentesis: Pain, Maximum Mouth Opening, Clicking/Crepitation. METHOD: Eleven patients who reported to the department of Oral and Maxillofacial Surgery, M S Ramaiah Dental College, Bangalore clinically diagnosed to have Internal Derangement of the TMJ underwent Arthrocentesis. Patients were evaluated at the end of 1 week, 1 and 3 months and results tabulated. RESULTS: 11 patients with clinically diagnosed Internal Derangement underwent Arthrocentesis and were followed up for 3 months. There was significant improvement in Pain, Maximum Mouth Opening and Clicking/Crepitation. All the results were statistically significant. There was no serious post operative complication. CONCLUSION: Arthrocentesis can be recommended as a simple chair-side procedure for the treatment of TMJ Internal Derangement refractory to conservative management.